2015
DOI: 10.1002/fsn3.242
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading the quality of Africa's rice: a novel artisanal parboiling technology for rice processors in sub‐Saharan Africa

Abstract: In order to increase the quality of locally produced rice, the artisanal parboiling process in West and Central Africa was reconceptualized. A novel parboiling unit was constructed using stainless steel (Inox 304) and fitted directly on an improved stove made from fired bricks. The heat profile at different locations in the unit, the physicochemical properties, cooking properties of the parboiled rice, and the fuel efficiency of the stove were evaluated and compared with that of the traditional system. The hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 28 publications
4
45
0
1
Order By: Relevance
“…() reported on changes in thiamine and riboflavin content in parboiled rice. However, the maximum steaming time used for that study was 12 min which was lower than what is used by rice processors in the region (Ndindeng et al., ). As it has been demonstrated that, during parboiling, the water‐soluble nutrients diffuse from the husk and outer layer of the rice grain into the endosperm with some authors proposing parboiling as a method of rice fortification (Fukai, Godwin, Rerkasem, & Huang, ; Rerkasem, Cakmak, & Huang, ), it is important to demonstrate how increasing steaming time affects physicochemical and nutritional properties of different rice varieties.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…() reported on changes in thiamine and riboflavin content in parboiled rice. However, the maximum steaming time used for that study was 12 min which was lower than what is used by rice processors in the region (Ndindeng et al., ). As it has been demonstrated that, during parboiling, the water‐soluble nutrients diffuse from the husk and outer layer of the rice grain into the endosperm with some authors proposing parboiling as a method of rice fortification (Fukai, Godwin, Rerkasem, & Huang, ; Rerkasem, Cakmak, & Huang, ), it is important to demonstrate how increasing steaming time affects physicochemical and nutritional properties of different rice varieties.…”
Section: Introductionmentioning
confidence: 81%
“…Several rice varieties have been developed for different rice production systems. In addition, good practices (agronomic and postharvest) including mechanization options are also being developed or adapted to increase the quantity and quality of locally produced rice (Amponsah, Addo, Dzisi, Moreira, & Ndindeng, ; Ndindeng et al., ; Saito et al., ). It is worth noting that most technologies have not reached most end‐users to produce the desired impact.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cette qualité « inférieure » du riz blanc local, due aux pratiques post-récolte peu appropriées utilisées par les riziculteurs et les transformateurs, peut être améliorée grâce à l'étuvage. En effet, l'étuvage, qui consiste à ré-humidifier, chauffer et sécher le paddy avant le décorticage, permet d'obtenir un riz de qualité physique, organoleptique et nutritionnelle supérieure à celle du riz blanc (Houssou et al, 2016 ;Ndindeng et al, 2015).…”
Section: Introductionunclassified